A genomic locus uniquely encoded by blueberry-infecting Xylella fastidiosa strains affects motility and biofilm formation in vitro, and virulence in planta - Navdeep Kaur; Marcus V. Merfa; Alexandra K. Kahn; Rodrigo P. P. Almeida; Leonardo De La Fuente (PLoS ONE, 2026)
Xylella fastidiosa ( Xf ) is an insect-transmitted, xylem-limited bacterial plant pathogen that infects hundreds of plant species. This pathogen causes bacterial leaf scorch in southern highbush blueberry ( Vaccinium corymbosum interspecific hybrids) in the southeastern United States, a disease that has not yet been reported elsewhere. Previously, a comparative genomic analysis of Xf and ancestral host species identified evolutionary events of gene gain and loss related to host range specificity. Here, by using a similar workflow, we identified two loci that are significantly found in blueberry-infecting strains. Locus_1088 included a hypothetical protein and a small part of the N-terminus of an orphan RelE toxin, while Locus_2741 was annotated as a hypothetical protein. Using a protocol based on natural competence, mutants were generated in three Xf subsp. multiplex strains from blueberry. Less biofilm, more planktonic growth, and increased twitching motility as compared to its wild-type (WT) were observed for the strain LA-Y3C_1088 mutant. In blueberry virulence assays, the LA-Y3C_1088 mutant caused significantly more severe symptoms than LA-Y3C_WT, whereas no significant differences were observed for other mutated strains. Interestingly the mutation of Locus_1088 additionally disrupted a toxin (part of a toxin-antitoxin system) that is likely responsible for the phenotypic changes observed. However, because the two independent mutants were not generated, we could not determine whether the phenotype resulted from disruption of hypothetical protein or the toxin. Additionally, since the coffee-isolated but never tested in blueberry Xf subsp. fastidiosa strain CFBP8073 was found to encode the two blueberry-associated loci studied here, its virulence was assessed in blueberry. This strain caused severe symptoms comparable to the control strain AlmaEm3 from blueberry. Due to the complexity of understanding host specificity in Xf, any advance in identifying genetic markers for host specificity in this devastating pathogen could greatly improve management of Xf worldwide.